RELEVANSI KONSEP BUDAYA ISLAM MENURUT ALI AHMAD MADZKUR DALAM PENDIDIKAN ISLAM KONTEMPORER - Mulyadi; Arwani, Muhammad; Hilmi, Irpan; Nurjanah, Naih; Syafei, Isop; Izzudin Musthafa (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the fundamental concept of Islamic culture according to Ali Ahmad Madzkur, analyze its core principles and values, explain the classification and characteristics of Islamic culture from his perspective, and explore the relevance of these ideas to the development of contemporary Muslim society within the social, cultural, and civilizational dynamics of the modern Islamic world. This research employs a descriptive qualitative approach to systematically describe and analyze Madzkur’s thought on Islamic culture. Primary data were obtained from Madzkur’s original works, while secondary data were gathered from supporting literature. Data collection was conducted through library research and subsequently analyzed using content analysis through data reduction, categorization, interpretation, and presentation to identify the relevance of Madzkur’s ideas for contemporary Muslim society. The findings indicate that Ali Ahmad Madzkur asserts that Islamic culture is rooted in divine revelation and encompasses the values of monotheism (tawhid), ethics, justice, and spiritual-material balance. Islamic culture is dynamic, adaptable to changing times, and categorized into the dimensions of creed, ethics, and knowledge. His ideas are relevant in responding to secular globalization by offering a divine cultural paradigm that remains open to scientific advancement and the development of modern Islamic civilization.